The Amplatzer Vascular Plug: Review of Evolution and Current Applications - Lopera, Jorge E. (Seminars in Interventional Radiology, 2015)
The Amplatzer Vascular Plug (AVP) was created for peripheral embolization as a modification of the family of Amplatz septal occluders used in the treatment of congenital heart malformations. The device has evolved over the years and multiple versions have been launched into the market. Each of the versions of the device has some important modifications in terms of the size of the introducer's system, number of layers, and resultant thrombogenicity. It is very important for the operator to become familiar with the unique features of the AVP, and to understand the advantages and limitations of each model in the AVP family to achieve an optimal embolic result. The purpose of this article is to review the evolution and current clinical applications of the AVP in the field of interventional radiology, with emphasis on the advantages and limitations of this device in comparison with other embolization agents.
Keywords: Amplatzer Vascular Plug; embolization; coils; arteriovenous fistulas; interventional radiology